Carbon Quantum Dots for Biomedical Applications: Review and Analysis - Azam, Nayab; Najabat Ali, Murtaza; Javaid Khan, Tooba (Frontiers in Materials, 2021)
Carbon quantum dots (CQDs) are a new type of nanocarbons that are currently favored over semiconductor quantum dots (QDs) because of their solubility, low toxicity, eco-friendly, cheap and facile synthesis giving desired optical characteristics. Moreover, their physiochemical properties can be controlled by its synthetic route. CQDs can emit fluorescence in the range from UV to near infrared (NIR) region making it suitable for biomedical applications. Fluorescence in these nanocarbons can be tuned by varying the excitation wavelength. As of now, CQDs have been used in various applications such as bioimaging, biosensing and drug-delivery. This article highlights the current progress and advancement of CQDs with focus on their chemical and optical properties, their synthetic routes and biomedical applications along with new perceptions in this interesting and promising field.